Relationship between strength, speed and change direction performance in field hockey players - Ibrahim Hassan, I. H. (MOJ Sports Medicine, 2018)
The aim of current study was to investigate the relationship between strength and linear or non-linear sprint performance variables in U19 male field hockey players during the midseason time. Twenty eight players from Sharkia Hockey Club participated in current study with anthropometric data of mean±SD (age=17.57±1.23 years, height=1.71±0.05 meter, body weight=66.05±5.93 kg and body mass index=22.61±1.78 kg/m2). Participants were measured for lower limb strength (vertical height jump, power and standing long jump), liner sprint (sprint over 30meters with different short distance included) and non-linear sprint performance (L running and zigzag measures). The relationships between physical fitness qualities were assessed by Pearson product-moment correlation coefficient. There were a moderate relationship between VJ height and sprint 20m and 30m performances, (r=0.66 and 0.63), respectively. Likewise, similar moderate relationships observed between power and sprint 20m and 30m performances (r=0.62 and 0.61), respectively. In addition, no significant relationships observed with other sprint distances or change of direction measures when correlated to other variables of VJ and power results. The study concluded that, the knowledge of relationships between strength and cyclic or acyclic sprint performances at various distances would allow coaches to structure the field hockey training drills.